TILSHUNOSLIKDA TERMIN, TERMINOLOGIYA, TERMINOLOGIK MAYDON TUSHUNCHALARINING O’Z-ARO FARQLANISHI XUSUSIDA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This thesis reflects the issues of mutual differentiation and demarcation of the term, terminology, terminological field, terminology system and Uzbek language «term» and term «atama» related to linguistics.
Keywords: term, terminology, terminological field, terminosystem, term «atama».